Choosing Representatives to Deliver the Message in a Group Violence Intervention. (3rd July 2019) - Wheeler, Andrew P.; McLean, Sarah J.; Becker, Kelly J.; Worden, Robert E.
Abstract: The group-based violence intervention model is predicated on the assumption that individuals who hear credible messages of consequences for further violence will deliver the message to other group members. Using social network analysis, we develop an algorithm of who should receive the message to maximize the spread of the message among the remaining group members. Using a sample of gangs in four different cities we show how the reach of actual call-ins were suboptimal compared to our suggested algorithm. Using simulations, we further show that typically only around a third of the group needs to be delivered the message to achieve complete coverage of the network. We find that even when limiting possible invitees to those under supervision large proportions of groups can be reached if the invitee list is data driven.